Cyclic loading test on a locally post-tensioned precast concrete beam–column connection. Issue 12 (September 2019) - Guan, Dongzhi; Yang, Hui; Ju, Dan; Guo, Zhengxing; Yang, Sen
A novel precast concrete beam–column connection locally post-tensioned using arc-shaped prestressing bars was proposed for satisfactory seismic performance and rapid construction. Three full-scale cruciform specimens, including one monolithic reference specimen, were tested under reversal cyclic loadings to evaluate the seismic behaviours. Grade 630 steel rods and high-strength deformed steel rebars were used for the arc-shaped prestressing bars in the precast specimens. The results show that the proposed precast connection presents an acceptable seismic performance and that the structural details should be ameliorated to improve the energy dissipation capacity. The design philosophy of strong column-weak beam is applicable to the new precast system. Finally, a strut-and-tie model was developed to investigate the force transfer mechanism of the novel precast connection.